PENGEMBANGAN MODUL IPA BERBASIS KEARIFAN LOKAL KOPI PADA POKOK BAHASAN USAHA DAN ENERGI DI SMP - Aida Nurul Safitri; Subiki Subiki; Sri Wahyuni (FKIP Universitas Jember, 2018)
AbstractScience module based on local wisdom of coffee was an alternative on developlearning tools by integrating local wisdom into science materials. This research wasa development research using Plomp development model that was adjusted into 4phases. The purposes of this research were to describe the validity of science modulebased on local wisdom of coffee, effectiveness and student's response. Theeffectiveness of science module was calculated from aspects of cognitive learningresult and student learning acitivities. The data collection methods were validation,test, observation, questionnaire and documentation. Science module based on localwisdom of coffee on material work and energy in Junior High School was valid withfinal validation result 4.39. Field trials were conducted in class VIIIA Argopuro 2Suci Junior High School with total of 39 students. The result of classical learningachievement was 82.05% and total percentage of student learning activity was84.33% with very active category. Both values indicate that science modules basedon local wisdom of coffee on material work and energy in Junior High School effectivewere viewed from aspects of learning result and student learning activities. Thenstudent's response got very good response with percentage of response was 84.62%.Keywords: Science module, local wisdom, validity, effectiveness, student’s response